EFEKTIVITAS PENGGUNAAN NEW MEDIA OLEH OMBUDSMAN RI PERWAKILAN KALIMANTAN TIMUR DALAM PENGELOLAAN PENGADUAN MASYARAKAT PASCA PEMINDAHAN IBU KOTA NEGARA - Hamzah Fansuri; Mujahid Mujahid; Nur Alim Djalil (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
This study aims to analyze the effectiveness of communication through new media (email, social media, whatsapp), based on the statements of Tubb and Moss. In addition, this study also analyzes the supporting and inhibiting factors of communication using these new media. The study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation. The results of this study show that the use of new media by the East Kalimantan Representative of the Indonesian Ombudsman is overall quite effective, specifically for WhatsApp usage is considered very effective, however, there needs to be an increase in the intensity of socialization of new media as a complaint channel on social media (Facebook and Instagram).The process of clarification and confirmation by the Ombudsman staff on messages is carried out quickly, accurately, and professionally, which becomes a supporting factor for the use of new media. The inhibiting factors are the spread of the network and equipment constraints. This study recommends that the Indonesian Ombudsman Representative in East Kalimantan can enhance cooperation with public service organizations and continue to improve the use of new media by conducting training and upgrading sufficient supporting resources/equipment.